Suggested Cut-Off Values for Vitamin D as a Risk Marker for Total and Cardiac Death in Patients with Suspected Acute Coronary Syndrome - Naesgaard, Patrycja A.; León de la Fuente, Ricardo A.; Nilsen, Stein Tore; Pönitz, Volker; Brügger-Andersen, Trygve; Grundt, Heidi; Staines, Harry; Nilsen, Dennis W. T. (Frontiers in Cardiovascular Medicine, 2016)
Background: Several studies have demonstrated an association between low vitamin D levels and cardiovascular risk. Vitamin D cut off levels are still under debate. Objectives: To assess two cut-off levels, 40 nmol/L and 70 nmol/L, respectively, for vitamin D measured as 25-hydroxyvitamin D [25(OH)D] in chest pain patients with suspected acute coronary syndrome. Methods: We investigated 1853 patients from coastal-Norway and inland Northern-Argentina. A similar database was used for pooling of data. 2-year follow-up data including all-cause mortality, cardiac death and sudden cardiac death in the total patient population were analyzed, applying univariate and multivariable analysis. Results: 255 patients with known vitamin D concentrations died. In the multivariable analysis, there was a decrease in total mortality above a cut-off level of 40 nmol/L and a decrease in cardiac death above a cut-off level of 70 nmol/L, [HRs of 0.66 (95% CI, 0.50 – 0.88), p = 0.004 and 0.46 (95% CI, 0.22 – 0.94), p = 0.034, respectively]. Conclusion: Vitamin D cut-off levels of 40 nmol/L and 70 nmol/L, were related to total mortality and cardiac death, respectively.